Psychosocial risks and labor stress in workers of the petroleum derivatives company of energy gas - Ecuador (Horizontes de Enfermería, 2019)
This research evaluated the presence, frequency, and intensity of psychosocial risk factors in relation to work stress on workers of Petroleum Derivatives Service Stations (PDSS) in the Energy Gas Company. The aim was to evaluate the relationship between Psychosocial Risk Factors and Work Stress in a population of 180 workers who perform different tasks in service stations. It was applied the Sociodemographic Survey and the Stress Evaluation-Third Version Questionnaire of the Pontificia Universidad Javeriana of Bogotá; and, the instrument of Psychosocial Factors at Work 20041 (Adapted). Among the results, psychosocial factors at work were presented with a high level in the PDSS: Work demands (89.0%): Workplace conditions (74.4%); Labor role - Career Development (72.9%); and, Content - Career Characteristics (70.5%). For work stress it was observed that physiological symptoms are at a high level (51.4%) and intellect labor symptoms (45.7%); concluding that psychosocial factors directly affect the appearance of Work Stress on the PDSS workers.
Keywords: Psychosocial risk factors; workplace stres; service stations workers